Association between urinary albumin-to-creatinine ratio within normal range and kidney stones in U.S. adults: a cross-sectional observational study - Du, Yuan-Zhuo; Zhang, Chi-Teng; Zeng, De-Ming; Li, Yong; Liu, Yi-Fu (Frontiers in Endocrinology, 2025)
BackgroundKidney stones are a major public health concern, and their prevalence has increased significantly in recent decades. While urinary albumin-to-creatinine ratio (UACR) is a recognized marker for kidney disease, its relationship with kidney stones, especially within the normal UACR range, remains unclear. The purpose of this study was to investigate the association between UACR levels within the normal range and the risk of developing kidney stones.MethodsWe analyzed data from the National Health and Nutrition Examination Survey (NHANES) conducted from 2009 to 2018, focusing on adults aged 20 years and older with available UACR data. Using weighted multivariable logistic regression and restricted cubic spline (RCS) models, we assessed the relationship between UACR levels and the prevalence of kidney stones, adjusting for relevant covariates. Subgroup analyses were also performed to evaluate the consistency of this association across demographic and health-related factors.ResultsThe study found that higher UACR levels within the normal range were significantly associated with an increased likelihood of developing kidney stones. Specifically, individuals in the highest quartile of UACR had a 36% higher odds of kidney stones compared to those in the lowest quartile (OR: 1.36, 95% CI: 1.04-1.77). A non-linear, dose-response relationship was observed between UACR levels and kidney stone risk (P < 0.001), with the association remaining consistent across various demographic subgroups.ConclusionElevated UACR levels, even within the normal range, are strongly associated with a higher risk of kidney stones. This finding highlights the potential of UACR as a valuable biomarker for assessing kidney stone risk in clinical practice.